Progress in nanomedicine for sonodynamic immunotherapy of tumors - Ziyan Feng; Ziyao Wang; Xi Xiang; Liyun Wang; Fangxue Du; Xueyang Xiao; Bihui Zhu; Xiao Rong; Li Qiu (EngMedicine)
Cancer remains a leading cause of mortality worldwide, with conventional treatments, such as chemotherapy and immunotherapy, exhibiting limitations, such as drug resistance and immune evasion. Therefore, novel therapeutic strategies are required. Sonodynamic therapy has emerged as an innovative approach in which sonosensitizers are activated by ultrasound to achieve antitumor effects through mechanisms, such as cavitation, thermal effects, and reactive oxygen species generation. Notably, sonodynamic therapy also exhibits immunomodulatory effects and strongly impacts the tumor microenvironment and immune system in the body. The immune effects of sonodynamic therapy indicate that it can be applied with immunotherapy to exert synergistic effects. This review describes the design of sonosensitizers and basic mechanisms of sonodynamic therapy, highlighting their immune effects and recent advancements in sonodynamic therapy-based cancer immunotherapy. In addition, we introduce the applications of gas and metabolic regulation therapies in sonodynamic immunotherapy.